Effects of Riming on Ice‐Phase Precipitation Growth and Transport Over an Orographic Barrier - Andrew DeLaFrance; Lynn A. McMurdie; Angela K. Rowe; Robert Conrick (Journal of Advances in Modeling Earth Systems, 2024)
Abstract The evolution of ice‐phase particles within precipitating clouds depends on the environmental properties of the cloud and on physical characteristics of the particles themselves, which can be modified by airflow over steep terrain. Through employing a unique Lagrangian particle‐based precipitation model, this study investigates the sensitivities in ice‐phase particle growth and transport due to variabilities in riming processes over an orographic barrier. This analysis is applied to two wintertime stratiform cyclones sampled by in situ aircraft over windward slopes during the Olympic Mountains Experiment. For both events, we simulate the ice‐phase particle evolution and trajectory within a two‐dimensional prescribed state representative of median observed cloud properties. Sensitivity simulations were constructed based on observed variabilities in supercooled liquid water (SLW) properties and its vertical extent above the melting level. Perturbations of SLW concentration equivalent to the 85th and 15th percentiles of observed values, which typically amounted to a change of less than 0.05 g m−3, resulted in respective increases or decreases in the ice‐phase contribution to surface precipitation mass by as much as 50% and horizontal particle trajectories differences exceeding 10 km. Similar sensitivities were found in response to varying the vertical extent of SLW above the melting level and to adjustments in mean SLW droplet size. The significant precipitation response to small variations in cloud properties principally arises from changing rates of rime mass accumulation and correspondingly, increases in particle fall speed. Considerations for the numerical representation of the riming process and its complex effects on precipitation are discussed.